Considering treatment of Hallux Valgus - Llontop Vite, Carlos S. (1967)
Hallux valgus , common and unsightly foot deformation, apparent simplicity , is to present a complex etiopathogenic and therapeutic problem . The multiplicity of proposed techniques for correction and the diversity of etiological theories , undoubtedly pose a series of controversies uncertain solution . Hallux valgus , as any medical problem should be approached from a global point of view. It is extremely important then assess foot deformities therefore carry often personality disorders and often disabling nature so considerable stop all activity. Hallux valgus Often accompanied by other equally important deformations are of the hospital visit ; as flat feet , hammertoes , bursitis, etc. . This study brings into question the results of a series of operations by Hallux Volcus , performed at different ages and using different techniques , conducted at the Department of Traumatology and Orthopedic Pavilion 6 - III " Archbishop Loayza" Hospital. The material collected, corresponding to the cases seen during the decade between the years 1953-1962 . Stories have been completed with radiographic and operative reports . In many cases we controlled patients some time after surgery , all of which served as a basis for analyzing the results.